Implementation of the MSME Micro Financing Strategy Through a Murabahah Agreement at BSI KCP Bangkalan Trunojoyo - Amalna, Fika; Ardyansyah, Farid (JESI (Jurnal Ekonomi Syariah Indonesia), 2023)
This study analyzes murabahah financing to help ease the burden on customers and promote MSME businesses. In general, murabahah financing is given to customers for short-term financing to meet the needs of an item needed by the community. This research method uses a qualitative approach, namely research that describes events and all matters related to circumstances based on facts found in the field. This study uses primary and secondary data with data collection methods through observation and interviews. The findings from this study indicate that the strategy implemented by BSI KCP Trunojoyo Bangkalan can solve the problem, namely through Rescheduling, Reconditioning, and Restructuring. Management assistance, Novation (AYDA), subrogation, inclusion, liquidation under the hands of HT/FEO execution auctions, auction via court, execution auction via Basyarnas, execution auction via court.